Kemas Ulang Informasi Jajanan Tradisional di Kabupaten Pesisir Selatan - Sari, Yulvina Permata; Nurizzati, Nurizzati (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractThis paper aims to describe the repackaging of traditional snacks information in the Kabupaten Pesisir Selatan. The method used is descriptive research method by collecting data through interviews conducted with traditional hawkers in the southern coastal districts. based on the discussion can be concluded stages in packing traditional snack information in the south coast district as follows. first, a typical type of traditional snacks in the southern coastal district consisting of 5 types of snacks. second, repackaging traditional snacks information in Kabupaten Pesisir Selatan has maps and book designs, the stages are as follows: (1) Identifying user needs, (2) Collecting information and selecting information sources, (3) Selecting sources that contain information value useful, (4) evaluating information validity, (5) reviewing, analyzing, extracting information into a more efficient form for users, (6) repacking information into a form that suits the needs of users, (7) distributing information in a promotional manner. (b) Coverage, (3) Preface, (4) Table of Contents, (5) Book Contents, (6) ClosureKeyword: Information packaging, traditional snack, Kabupaten Pesisir Selatan